Active factor investing: Hedge funds versus the rest of us. Issue 4 (12th September 2020) - Duanmu, Jun; Li, Yongjia; Malakhov, Alexey
Abstract: We examine whether the success of hedge fund market timing strategies can be replicated. We develop a methodology for creating a portfolio of ETFs to capture risk factor exposures of market timing hedge funds identified using extant market timing measures. We find that the top market timing hedge funds outperform their ETF clone peers and the superior performance cannot be replicated. We show that the irreplicable market timing skills are more profound in certain hedge fund styles. Finally, we provide evidence that the success of market timing strategies is driven by non‐cloneable hedge funds that possess managerial skills.